Cord blood hematological reference values in term and late preterm infants from the Mediterranean island of Sardinia: a preliminary study - Francesco Ronchi; Annalisa Porcella; Pietro Paolo Porcu; Sergio Salis; Cristian Locci; Nadia Vacca; Claudio Fozza; Roberto Antonucci (Hygeia Press di Corridori Marinella, 2020)
Background: Even though umbilical cord blood (UCB) has become an important source of hematopoietic stem cells for transplant, little is known about normal hematological values at birth. The aim of our preliminary retrospective study was to determine reference values for the main hematological parameters of UCB, stratified by gender, gestational age and delivery route in the Sardinian neonatal population. Method: In our retrospective study we reviewed hematological blood counts from UCB samples collected consecutively at the Neonatal and Obstetric Division of San Gavino Hospital, Sardinia, Italy, between January 1, 2013, and June 30, 2014. Unsuitable samples (insufficient blood amount, clotted or hemolyzed samples) were excluded from the analysis. Results: A total of 439 UCB samples from newborn infants with gestational age ranging from 34 to 42 weeks were included in the study. Newborn infants from vaginal delivery and preterm infants showed higher erythrocyte and leukocytes values, while no differences in hematological values were found between males and females. Interestingly, reticulocyte hemoglobin content was specifically evaluated and its values were found not to be influenced by gender, gestational age, and delivery route. Conclusions: These preliminary findings may contribute to define reference values for UCB hematological parameters in term and late preterm infants from the Mediterranean island of Sardinia, thus favoring a wider use of these parameters in the clinical management of the newborn.